Modeling of magnetoliposome uptake in human pancreatic tumor cells in vitro. (20th February 2019) - Slabu, Ioana; Roeth, Anjali A; Engelmann, Ulrich M; Wiekhorst, Frank; Buhl, Eva M; Neumann, Ulf P; Schmitz-Rode, Thomas
Abstract: The internalization kinetics resulting from magnetic nanoparticle interactions with tumor cells play an important role in nanoparticle-based cancer treatment efficiency. Here, the uptake kinetics of magnetoliposomes (ML) into human pancreatic tumor cells (MiaPaCa-2 and BxPC-3) are quantified using magnetic particle spectrometry. A comparison to the uptake kinetics for healthy L929 cells is given. The experimental results are used for the development of an uptake kinetics model describing the three relevant internalization processes: ML adsorption to the cell membrane, endo- and exocytosis. By fitting of experimental data, the rate constant of each internalization process is determined enabling the prediction of internalized ML at any incubation time. After seven hours incubation time, MiaPaCa-2 internalized three times more ML than BxPC-3 and L929 cells even though their ML adsorption rate constants were nearly the same. As the interaction of the ML with the cell membrane is non-specific, the uptake kinetics mirror the individual cell response to ML internalization. With a new mathematical term to cover the exocytosis contribution to the overall internalization process, the extended uptake kinetics model offers new possibilities to analyze the specific internalization mechanism for other nanoparticle and cell types.